2020
DOI: 10.1186/s12883-020-01951-6
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of stroke-related knowledge among community residents and the improvement after intensive health education: a cross-sectional study

Abstract: Background The high morbidity, mortality, and disability rates of stroke constitute a heavy burden to the society. The level of understanding about stroke warning symptoms and first aid systems among community residents was generally low. The aim of our work is to investigate stroke-related knowledge in community residents of Jinjiang district of Chengdu and to raise public awareness about stroke through an intensive educational program. Methods Nine communities in Jinjiang district were sampled and a questi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…It is important to note that there was no significant association between knowledge of stroke and the decision to call an ambulance in our study which is in agreement with a study conducted in Ireland (47). However, this differs from Lackland's et al study which revealed a decline in stroke mortality in the US that was attributed to the implementation of interventions and programs resulting in better knowledge of stroke risk factors, hence improving stroke practice (38)(39)(40)(41)(42). Also, our findings showed a positive relationship between having a medical history of atrial fibrillation and heart attack which is a finding that differs from a study conducted in Ireland where no association was found with the presence of any diagnosis of cardiovascular diseases (47) and another research in the US where a positive relationship was seen in participants with no prior history of heart attack (45).…”
Section: Response To Strokesupporting
confidence: 87%
See 2 more Smart Citations
“…It is important to note that there was no significant association between knowledge of stroke and the decision to call an ambulance in our study which is in agreement with a study conducted in Ireland (47). However, this differs from Lackland's et al study which revealed a decline in stroke mortality in the US that was attributed to the implementation of interventions and programs resulting in better knowledge of stroke risk factors, hence improving stroke practice (38)(39)(40)(41)(42). Also, our findings showed a positive relationship between having a medical history of atrial fibrillation and heart attack which is a finding that differs from a study conducted in Ireland where no association was found with the presence of any diagnosis of cardiovascular diseases (47) and another research in the US where a positive relationship was seen in participants with no prior history of heart attack (45).…”
Section: Response To Strokesupporting
confidence: 87%
“…Moreover, Alreshidi et al revealed that the majority of the Saudi population showed poor stroke risk factors and warning signs knowledge leading to insufficient KAP in 63.8% of the participants (36). Consequently, in primary stroke prevention, awareness is the first approach to diminish stroke incidence in the general public (37)(38)(39)(40)(41). Knowledge of stroke risk factors and warning signs is necessary in stroke prevention as well as the readiness in implementing prevention measures (37)(38)(39)(40)(41)(42).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The OTD stability can be traced back to a level of patients/caregivers’ education still not enough to timely recognize stroke signs and symptoms resulting in a delayed request for emergency healthcare. Some Authors recently underlined the need for enhancing patient awareness on timely emergence medical services usage at stroke onset by strengthening publicity and educational activities [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…AIS treatment involves pre-hospital identi cation, evaluation, and treatment; secondary prevention; rehabilitation; and other procedures. A few studies [6,7] have reported that the prevention and treatment ability of Chinese community doctors required improvement. Only when these doctors fully grasp the principles of diagnosis and treatment can patients receive the most timely and appropriate treatment.…”
Section: Introductionmentioning
confidence: 99%